Diseño de Jardines de Conservacion In Situ, en el bosque Siempre Verde Montano de la Cordillera Occidental de los Andes (bsmn03), en la Provincia de Cotopaxi-Canton Pujilí Parroquia El Tingo-La Esperanza, a 2000-3100 msnm, en el periodo 2018-2019 - Pullotasig Arequipa, Viviana Alexandra (2019)
This document details the study carried out in the Cotopaxi Province, Pujilí Canton El Tingo-La Esperanza Parish, located in the foothills of the western mountain range of the Andes in a mountainous area at an altitude between 2000-3100 at the sea level, whose center is the mountain range of Yungañan and at its end forms the hydrological system of the river Pilalo joining this with the Quindigua River forming the Quevedo River. Being to 90 km of the cantonal head of Pujili which counts on a temperate and sub-tropical climate. According to studies, it is a place that has 3 types of ecosystems, with floristic species of economic and environmental value, this work is linked to one of the specific objectives of the project "Recovery of germplasm of plant species of the north-western area of Cotopaxi Province", which is: Implement in situ conservation gardens where methodologies were developed to help establish in situ conservation gardens, delimited in this way a quadrant of (60x60m2), within the quadrant was made divisions of 15 m both horizontal and vertical obtaining a total of 16 quadrants. In each of the quadrants it is suggested to place tree species at 3 m and shrub species at 2 m alternately between the two species, planting in each of the quadrants 16 species. Each quadrant consisted of 128 arboreal and shrub species giving us a total of 256 species for this reason a plot of 10mx 20m (200m2) was traced to a height of 1830 meters above sea level by sampling in the form of a simple continuous zigzag, applying the method of rapid ecological assessment that allowed to visualize the state of the area to investigate, thus helping to collect tree and shrub species with a diameter equal to or greater than 2.5cm DBH (Diameter at Chest Height). For this design it is suggested to use the technique of forest enrichment thus helping to conserve the biodiversity that exists in the evergreen montane forest located in an area of variable origin among its vegetation that are important for phylogenetic improvement. The present work intended to restore the degraded forests of the area.